Graph y = 2x – 3 <br />
Graph y = -3x + 1 <br />
Graph 4x + 2y = 4<br />4(0) + 2y = 4<br />0 + 2y = 4<br />2y = 4<br /> 2    2<br />y = 2<br />
Graph 4x + 2y = 4<br />4(1) + 2y = 4<br />4 + 2y = 4<br />-4	     -4<br />     2y = 0<br />      2    2<br />       y = 0<...
Graph 4x + 2y = 4<br />4(2) + 2y = 4<br />8 + 2y = 4<br />-8	     -8<br />     2y = -4<br />      2    2<br />       y = -...
Graph 4x + 2y = 4<br />4(3) + 2y = 4<br />12 + 2y = 4<br />-12	     -12<br />     2y = -8<br />      2    2<br />       y ...
Graph 4x + 2y = 4<br />
Graph x – y = -1<br />0 – y = -1<br />   – y = -1<br />     -1    -1<br />y = 1<br />
Graph x – y = -1<br />1 – y = -1<br />-1	    -1<br />   – y = -2<br />     -1    -1<br />y = 2<br />
Graph x – y = -1<br />2 – y = -1<br />-2	    -2<br />   – y = -3<br />     -1    -1<br />y = 3<br />
Graph x – y = -1<br />3 – y = -1<br />-3	    -3<br />   – y = -4<br />     -1    -1<br />y = 4<br />
Graph x – y = -1<br />
Upcoming SlideShare
Loading in …5
×

Alg1 lesson 4-5

505 views

Published on

Published in: Education
0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total views
505
On SlideShare
0
From Embeds
0
Number of Embeds
2
Actions
Shares
0
Downloads
0
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide

Alg1 lesson 4-5

  1. 1. Graph y = 2x – 3 <br />
  2. 2. Graph y = -3x + 1 <br />
  3. 3. Graph 4x + 2y = 4<br />4(0) + 2y = 4<br />0 + 2y = 4<br />2y = 4<br /> 2 2<br />y = 2<br />
  4. 4. Graph 4x + 2y = 4<br />4(1) + 2y = 4<br />4 + 2y = 4<br />-4 -4<br /> 2y = 0<br /> 2 2<br /> y = 0<br />
  5. 5. Graph 4x + 2y = 4<br />4(2) + 2y = 4<br />8 + 2y = 4<br />-8 -8<br /> 2y = -4<br /> 2 2<br /> y = -2<br />
  6. 6. Graph 4x + 2y = 4<br />4(3) + 2y = 4<br />12 + 2y = 4<br />-12 -12<br /> 2y = -8<br /> 2 2<br /> y = -4<br />
  7. 7. Graph 4x + 2y = 4<br />
  8. 8. Graph x – y = -1<br />0 – y = -1<br /> – y = -1<br /> -1 -1<br />y = 1<br />
  9. 9. Graph x – y = -1<br />1 – y = -1<br />-1 -1<br /> – y = -2<br /> -1 -1<br />y = 2<br />
  10. 10. Graph x – y = -1<br />2 – y = -1<br />-2 -2<br /> – y = -3<br /> -1 -1<br />y = 3<br />
  11. 11. Graph x – y = -1<br />3 – y = -1<br />-3 -3<br /> – y = -4<br /> -1 -1<br />y = 4<br />
  12. 12. Graph x – y = -1<br />

×